2014
DOI: 10.1371/journal.pone.0091259
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Function for Kojic Acid, a Secondary Metabolite from Aspergillus Fungi, as Antileishmanial Agent

Abstract: Kojic acid (KA) is a fungal metabolite used as a topical treatment skin-whitening cosmetic agent for melasma in humans; however its potential as an anti-leishmanial agent is unknown. Chemotherapy is one of the most effective treatments for Leishmaniasis. However, the drugs available are expensive, invasive, require long-term treatment and have severe side effects. Thus, the development of new effective leishmanicidal agents is a necessity. In this study we investigated the anti-leishmanial effect of KA on L. a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 37 publications
(41 reference statements)
4
29
0
Order By: Relevance
“…Intracellular amastigotes are responsible for the clinical manifestations of leishmaniasis [37]. Considerable efforts have been done in searching for new substances that act on intracellular forms of Leishmania protozoa [38,39,40,41]. Alkaloids and derivatives have shown this effect, such as the diterpene alkaloid derivatives that exhibited antiproliferative action against amastigote forms of L. infantum without causing cytotoxic effects in host cells [42].…”
Section: Resultsmentioning
confidence: 99%
“…Intracellular amastigotes are responsible for the clinical manifestations of leishmaniasis [37]. Considerable efforts have been done in searching for new substances that act on intracellular forms of Leishmania protozoa [38,39,40,41]. Alkaloids and derivatives have shown this effect, such as the diterpene alkaloid derivatives that exhibited antiproliferative action against amastigote forms of L. infantum without causing cytotoxic effects in host cells [42].…”
Section: Resultsmentioning
confidence: 99%
“…Previous bioactivity studies on kojic acid (1) revealed its antioxidant [18], tyrosinase inhibitory [19], anti-pigmentation (skin whitening) [20,21], nematicidal [22], antifungal [23] and antileishmanial [24] properties. Kojic acid (1) is a chelation agent produced by several species of fungi, especially Aspergillus oryzae, which has the Japanese common name koji.…”
Section: Discussionmentioning
confidence: 99%
“…The approved and permitted maximum concentration of kojic acid (1) in cosmetic products, e.g., powders, serums, creams, cleansers, and soaps, is 1%. Some products, like soaps and cleansers, are meant to be washed off immediately, but others, like creams and serums, are formulated to be left on and absorbed into the skin [21][22][23][24]. Products containing kojic acid (1) are frequently used on the face and hands, but can be applied on all non-sensitive areas of the body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These side effects and disadvantages demonstrate the necessity to identify new, effective, and safe compounds for the treatment of this disease (Croft et al, 2006b;Rodrigues et al, 2014). The domestic dog is the main reservoir for the transmission of the visceral form of leishmaniasis, thereby accounting for its widespread occurrence in the human population (Courtenay et al, 2002).…”
Section: Discussionmentioning
confidence: 99%